Political-Economic Aspects of the Report on the Position of Consumers by the Advisory Council for Consumer Affairs (SVRV) - Gert G. Wagner (Wirtschaftsdienst, 2021)
Abstract For the first time, the German Advisory Council for Consumer Affairs (SVRV) has published a comprehensive report on the position of consumers in Germany. The author, who is a member of the SVRV, presents selected analyses, results and recommendations. Additionally, relevant events that have taken place after the report was completed are also mentioned: the presentation of the proposed EU regulation “Artificial Intelligence Act”, the climate protection ruling of the Federal Constitutional Court and the draft law on autonomous driving in Germany.